Using block copolymer architecture to achieve sub-10 nm periods. (14th July 2017) - Sun, Zhiwei; Zhang, Wenxu; Hong, Song; Chen, Zhenbin; Liu, Xiaohui; Xiao, Shuaigang; Coughlin, E. Bryan; Russell, Thomas P.
Abstract: Using salt-doped polystyrene- b -poly(2-vinylpyridine) star shaped block copolymer as a model, we show that the architecture of (A- b -B)n type multi-arm star block copolymers enhances the ordering of the block copolymers, enabling the generation of nanostructures with microdomain periods less than 10 nm. The influence of the arm number on the order-to-disorder transition temperature and molecular weight was systematically studied using small angle X-ray scattering. The configurational constraints placed on the chains by anchoring each block copolymer to a central junction point have a significant effect on the disorder-to-order transition behavior. In addition to an increase in the Flory-Huggins parameter ( χ ), block copolymers with multi-arm star shape chain architecture have a critical segregation strength ( χN )C that decreases with arm number, opening a simple route to generate ordered nanostructures with periods below 10 nm. Graphical abstract: This is a figure to show disorder-to-order transition happens with the increase of arm numbers in the star shaped block copolymer. Ordered lamellar morphology with 9 nm period was obtained in four-arm star shaped (PS- b -P2VP)4 block copolymer. Highlights: Proposed a new way to reduce the lower limit of block copolymer repeating period by changing polymer chain architecture. The disorder-to-order transition limit of block copolymer can be pushed downward by using chain architecture. By using four-arm star shape block copolymer, ordered lamellar nanostructures with 9.7 nm repeating periods are prepared.